Signifikansi Guru Pak Dalam Meningkatkan Kualitas Iman Dan Moralitas Peserta Didik Di Era Postmodernisme - Devi Kristi Susanti; Bennydektus Bennydektus; Yublina Kasse (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
One important theme that is rarely discussed is the service towards children. In community life, children are often neglected and deemed unimportant in certain contexts. Children have the smallest place in the social order of life. This is also experienced by children within the Christian community. They are only seen as the future of the church, leading to their current existence being often ignored. This should certainly be a matter of concern for all parties, including parents, pastors, and even Christian teachers or educators. The challenges faced by children in the postmodern era have become increasingly complex. They will confront a reality that perceives no absolute truth, as all truths are considered relative. Therefore, the core focus of this paper is to discuss the steps or roles that Christian religious education teachers take in preparing children, especially Christian children, to face this postmodern era. In the discussion, the author presents various challenges and needs of children in the postmodern era, as well as what a Christian educator should do. The method used by the author in this article is a literary method with a descriptive approach. The author gathers various data sources related to the discussed topic and analyzes them to find a comprehensive and accurate understanding. Through this research, it is found that a Christian religious education teacher is responsible for nurturing and guiding children to know Christ, so that they have faith, acknowledge Jesus as Lord and Savior, and experience a renewal of life.